Enlargement gingival treatment on teeth 11 and 21 - Umi G. Tjiptoningsih (Journal of Dentomaxillofacial Science, 2016)
Gingival enlargement in the interdental papillae, thickened, rounded gingival contour and discomfort became major issues that must be treated in order to be optimal appearance and function. Gingival enlargement that experienced fibrosis would not disappear with only plaque control, but required surgery that is gingivectomy and gingivoplasty. The 24-year-old woman came to the periodonsia clinic with complaints maxillary anterior gingiva swelled at teeth 11-21 with plaque index 52%. The depth of the tooth pocket 11: labial (mesial: 4, medial: 1, distal: 3). Palatal (mesial: 3, medial: 2, distal 1). The depth of the tooth pocket 21 is labial (mesial: 4, medial: 1, distal: 1), palatal (mesial: 3, medial: 1, distal 1). Gingivectomy treatment and gingivoplasty were performed with the aim of eliminating pockets and restore physiologic gingival contour which can help prevent the recurrence of the disease periodontal. In performing surgical gingivectomy and gingivoplasty, which must be considered is to minimize the disposal of gingival tissue to maintain the aesthetic, adequate access to the bone defect in order to make good corrections, and the minimization of bleeding and discomfort after surgery.